Analisis Gaya Drag Pada Mobil Sedan dengan Penambahan Komponen Drag Reduction - Aziz, Abdul; Nofriadi, Nofriadi; Rudianto, Rudianto; Alfi, Rizki; Naro, Aulia; Sumiati, Ruzita (Jurnal Teknik Mesin, 2025)
The aerodynamic design of a vehicle body plays a critical role in reducing air resistance (drag), thereby contributing to improved fuel efficiency. Aerodynamic resistance in vehicles is influenced by several parameters, including body geometry, auxiliary elements, and the orientation of the vehicle relative to the airflow. This study aims to analyze the effects of body shape variations and the addition of a spoiler on drag force reduction in a sedan-type vehicle. The methodology employed in this research is numerical simulation using Ansys Fluent software. Simulation results indicate that the model with a more streamlined geometry (Model C) produces a lower drag force compared to the model equipped with a spoiler. The drag coefficients obtained for each configuration are as follows: Sedan A — 0.780, Sedan B with a spoiler — 0.775, and Sedan C with an improved body geometry — 0.647. These findings suggest that optimizing body shape is more effective in enhancing the aerodynamic performance of a vehicle than the addition of external aerodynamic elements such as a spoiler.